In vitro effects of conditioned medium from bioreactor cultured human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) on skin-derived cell lines - Park, Yu Mi; Lee, MinJi; Jeon, SungHyun; Hrůzová, Dagmar (Regenerative therapy, 2021)
INTRODUCTION: When stem cells are grafted into tissues, they differentiate and form specialized cells. However, the proficiency of stem cells to endure and assimilate the host cell is dependent on various growth factors and cytokines. According to various studies, these factors are available in the spent media of harvested stem cells, which can be used for treatment in regenerative medicine and cosmetic products. There are differences in cytokine secretion depending on the culture environment, which are clarified in this paper. METHODS: Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) were cultured either in a bioreactor or in a flask. The conditioned medium from the hUC-MSC cultures in the flask and in the bioreactor was designated as "FM" and "BM", respectively. We assessed the effects of FM and BM on UVB-induced oxidative stress, anti-aging, and melanogenic properties. The amount of growth factors, cell viability, hyaluronic acid (HA), pro-collagen, and pro-melanin were quantitatively evaluated in the FM and BM treated groups. The induction of HA and collagen synthesis was measured in CCD-986SK cells. For melanogenesis, the effects of FM and BM on melanin content and tyrosinase activity were measured in SK-MEL-31 cells. RESULTS: In the present study, the secretion of growth factors, HA, and pro-collagen was significantly higher in the BM treatment, compared to that in the FM treatment. BM protected CCD-986SK cells against death from UVB induced oxidative stress. BM increased the promoter activity of the anti-oxidant genes SOD1, CAT, and GP; and downregulated the accelerating collagen decomposition gene, MMP-1, induced by UVB irradiation. In α-melanocyte-stimulating hormone (α-MSH) stimulated SK-MEL-31 cells, BM reduced melanin production and decreased the levels of MITF, tyrosinase, TRP-1, and TRP-2. These results suggest that BM could be used as a skin protection agent, because of its anti-apoptotic, anti-aging, and anti-melanogenic properties. This could be attributed to the differences in culturing methods; it is difficult to maintain the temperature and sterility in FM culture, when compared to that in the automated culturing conditions of the BM system. CONCLUSIONS: Collectively, our results indicate that using BM-conditioned hUC-MSC medium is very efficient process for producing raw materials for developing functional cosmetics.
Keywords: Growth factors; Human stem cell-conditioned medium; Melanogenesis; Anti-apoptosis; Anti-aging; Hyaluronic acid